The Wielding Influence of Political Networks: Representation in Majority-Latino Districts. (March 2018) - Ocampo, Angela X.
Latino-majority congressional districts are far more likely to elect Latino representatives to Congress than majority-white districts. However, not all majority-Latino districts do so. This paper addresses this question, and it investigates how the level of influence of political parties and interest groups in majority-Latino districts substantially shapes Latino representation to the US House of Representatives. I rely on five case studies and a dataset of candidates to open congressional races with a Latino population plurality from 2004 to 2014. The evidence indicates that groups and political networks are critical for Latina/o candidate recruitment, the organization of resources in a congressional district, the deployment of campaign resources on behalf of certain candidates, and the eventual success of Latina/o candidates. The findings suggest that Latino descriptive and substantive representation are shaped by the wielding influence of political parties and interest groups.